SEM-PLS Model of Resource Based ISO 56002;2019 Integrated Lean Six Sigma for Cultivating Culture of Innovation (Cased in Precast Concrete Company in Indonesia) - Ginting, Yan; Latief, Yusuf; Hidayanti, Ranti (Journal of International Conference Proceedings, 2023)
This study explores the integration of ISO 56002:2019-based Innovation Management Systems and Lean Six Sigma in the resource context of the precast concrete industry. Lean Six Sigma (LSS) and Innovation are powerful methodologies that exhibit several differences, there are numerous areas where LSS and innovation share compatible foundations and common goals in the pursuit of improving implementation of Innovation management system on these companies. In this study, we conducted a literature review to identify the research variables, which were then validated by 5 experts. We collected data through questionnaires from 54 respondents who work in a precast concrete company in Indonesia. SEM-PLS methods were used for analysis. Results indicate Lean Six Sigma's substantial positive influence on resource of precast concrete company in the Innovation Management System, offering valuable insights for Indonesia's precast concrete industry. This study contributes to continuous improvement in innovation culture, fostering competitiveness in the global market.